Molecular and functional characterization of the SBP-box transcription factor SPL-CNR in tomato fruit ripening and cell death. (4th February 2020) - Lai, Tongfei; Wang, Xiaohong; Ye, Bishun; Jin, Mingfei; Chen, Weiwei; Wang, Ying; Zhou, Yingying; Blanks, Andrew M; Gu, Mei; Zhang, Pengcheng; Zhang, Xinlian; Li, Chunyang; et al.
Abstract: SlSPL-CNR, an SBP-box transcription factor (TF) gene residing at the epimutant Colourless non-ripening ( Cnr ) locus, is involved in tomato ripening. This epimutant provides a unique model to investigate the (epi)genetic basis of fruit ripening. Here we report that SlSPL-CNR is a nucleus-localized protein with a distinct monopartite nuclear localization signal (NLS). It consists of four consecutive residues ' 30 KRKR33 ' at the N-terminus of the protein. Mutation of the NLS abolishes SlSPL-CNR's ability to localize in the nucleus. SlSPL-CNR comprises two zinc-finger motifs (ZFMs) within the C-terminal SBP-box domain. Both ZFMs contribute to zinc-binding activity. SlSPL-CNR can induce cell death in tomato and tobacco, dependent on its nuclear localization. However, the two ZFMs have differential impacts on SlSPL-CNR's induction of severe necrosis or mild necrotic ringspot. NLS and ZFM mutants cannot complement Cnr fruits to ripen. SlSPL-CNR interacts with SlSnRK1. Virus-induced SlSnRK1 silencing leads to reduction in expression of ripening-related genes and inhibits ripening in tomato. We conclude that SlSPL-CNR is a multifunctional protein that consists of a distinct monopartite NLS, binds to zinc, and interacts with SlSnRK1 to affect cell death and tomato fruit ripening. Abstract : The tomato transcription factor SlSPL-CNR is a multi-functional protein that has a role in fruit ripening and is capable of triggering cell death.